Differential diagnosis of gallstones by using hypericin as a fluorescent optical imaging agent - Miranda Cona, Marlein (World J Gastroenterol, 2016)
AIM: To explore the feasibility of using hypericin as an optical imaging probe with affinity for cholesterol for differential fluorescent detection of human gallstones. METHODS: Cholesterol, mixed and pigment stones from cholecystectomy patients were incubated with hypericin or solvent. After 72 h, the stones were analysed for fluorescence (365 nm) and treated with 2-propanol/dimethyl sulfoxide for high performance liquid chromatography (HPLC) analysis. Rats with virtual gallbladder containing human cholesterol, mixed or pigment gallstones (VGHG) received 5 mg/kg hypericin or solvent and VGHG rats with cholesterol stones were given different hypericin doses (5-15 mg/kg). Twelve hours later, the stones were analysed at 365 nm. Biliary excretion and metabolites of hypericin were assessed in common bile duct (CBD) cannulated rats for 9 h using fluorospectrometry, HPLC and matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS). RESULTS: Homogeneous high fluorescence was seen on cholesterol stones either pre-incubated with hypericin or extracted from VGHG rats receiving hypericin. Mixed stones showed a dotted fluorescent pattern, whereas pigment and solvent-treated ones lacked fluorescence. HPLC showed 7.68, 6.65 and 0.08 × 10(-3) M of cholesterol in extracts from cholesterol, mixed, and pigment gallstones, respectively. Hypericin accounted for 2.0, 0.5 and 0.2 × 10(-6) M in that order. On cholesterol stones from VGHG rats receiving different hypericin doses, a positive correlation was observed between dose and fluorescence. In the bile from CBD-cannulated rats, fluorescence represented 20% of the injected dose with two peaks in 9 h. HPLC analysis revealed that hypericin conjugates reached 60% of the peak area. By MALDI-TOF MS, hypericin-glucuronide was detected. CONCLUSION: This study proves the potential use of hypericin for differential fluorescent detection of human gallstones regarding their chemical composition.